Acute Proteomic Changes in the Lung After WTLI in a Mouse Model: Identification of Potential Initiating Events for Delayed Effects of Acute Radiation Exposure. Issue 4 (April 2019) - Huang, Weiliang; Yu, Jianshi; Jones, Jace W.; Carter, Claire L.; Jackson, I. Lauren; Vujaskovic, Zeljko; MacVittie, Thomas J.; Kane, Maureen A.
Abstract : Abstract: Radiation-induced lung injury is a delayed effect of acute radiation exposure resulting in pulmonary pneumonitis and fibrosis. Molecular mechanisms that lead to radiation-induced lung injury remain incompletely understood. Using a murine model of whole-thorax lung irradiation, C57BL/6J mice were irradiated at 8, 10, 12, and 14 Gy and assayed at day 1, 3, and 6 postexposure and compared to nonirradiated (sham) controls. Tryptic digests of lung tissues were analyzed by liquid chromatography-tandem mass spectrometry on a Waters nanoLC instrument coupled to a Thermo Scientific Q Exactive hybrid quadrupole-orbitrap mass spectrometer. Pathway and gene ontology analysis were performed with Qiagen Ingenuity, Panther GO, and DAVID databases. A number of trends were identified in the proteomic data, including protein changes greater than 10 fold, protein changes that were consistently up regulated or down regulated at all time points and dose levels interrogated, time and dose dependency of protein changes, canonical pathways affected by irradiation, changes in proteins that serve as upstream regulators, and proteins involved in key processes including inflammation, radiation, and retinoic acid signaling. The proteomic profiling conducted here represents an untargeted systems biology approach to identify acute molecular events that could potentially be initiating events for radiation-induced lung injury. Abstract : Supplemental digital content is available in the text.